VD_FINDINFO 3/2016/FAB vom 29. Februar 2016 - VD Tribunal cantonal (2016)
CONCORDAT SUR L'ARBITRAGE, CONVENTION D'ARBITRAGE | 11 C-Arb, 12 C-Arb, 13 C-Arb, 22 C-Arb, 23 C-Arb, 427 let. b CPC, 356 CPC (CH), 362 al. 1 CPC (CH)